Platform based Innovation Ecosystems: Value Network Configuration Perspective - Lähteenmäki Jarno; Töyli Juuso (Universidade do Porto - Faculdade de Engenharia, 2026)
A platform-based innovation ecosystem links multiple markets and their corresponding stakeholders for joint value creation and innovation around a platform, and it is critical for the platform sponsor to manage the configuration efficiently for maximized value and survival. Through a multi-case study, we propose a configurational framework for platform ecosystems to analyze multi-stakeholder business structures, boundary decisions and their relationships. We define the context as for-profit business networks that leverage a digital platform to create multi-sided market circumstances and to engage partners as well as customers in joint innovation and value creation. Empirically we study five small to mid-sized digital information and communication technology platforms and their ecosystems. The discoveries elaborate on the four characteristic configurations and activities involved in the platform ecosystem management, and show configurational differences between open, semi-open, and closed innovation ecosystems. We propose the value-network configurations for the ecosystem, upstream producer, downstream consumer, and partner driven scenarios. Contradicting the existing literature, we argue that complementarities are created by two different producer actors and the consumption is influenced by two different downstream actors. We also argue that an internal production platform can be considered a platform ecosystem for innovation in the case of the extensive use of external knowledge and resource sources. The results extend the understanding of a platform ecosystem as a multi-layered configuration, and show what are the roles of different functions in the multi-layered structure. © 2023 Journal of Innovation Management.